Snakes and Ladders Media to Improve Social Studies Learning Outcomes of Fifth Grade Elementary School Students - Rizkiana, Feri; Sari, Elok Fariha (Journal of Education Technology, 2024)
Less than optimal use of teaching and learning resources in the form of learning media can affect learning activities in schools, especially in social studies subjects. The purpose of this research is to produce snakes and ladders media on social studies subject material how the shape of my Indonesia grade V elementary school. This study uses the type of Research and Development research with Borg and Gall research and development model. There are two collection methods, namely test techniques using pretest and post-test, and non-test techniques carried out by observation, interviews, document data, and questionnaires or questionnaires. The data collection instrument in this research is a questionnaire instrument in the form of a rating scale that has been tested by media experts, material experts, practitioners, and students. There are two data analysis techniques in this study, namely quantitative descriptive analysis and qualitative descriptive analysis. This study through the data analysis process using the SPSS 26 application which includes several tests, namely, normality test, homogeneity test, t-test, and N-Gain test. The results of the study are snakes and ladders media on social studies learning material how the shape of my Indonesia is valid and obtained very good qualifications, as well as pretest and post-test learning outcomes on media trials, show significant differences and an average increase in student learning outcomes.